The Effect of Antifreeze Reagent on Seasonal Frozen Soils - Zhussupbekov, A. Z.; Montayeva, A. S.; Montayev, S. A. (Periodicals of Engineering and Natural Sciences. - 2021., 2021)
The design, construction, and maintenance of pile foundations are dependent on special weather conditions in Northern and Central part of Kazakhstan. The winter months in these areas are very long which starts from November to March and the air temperature usually reaches – 40-50°C. These circumstances lead to the seasonal freezing ground, special physical behavior of soil, physical properties of construction materials. The main problem of pile driving in winter is frozen ground which is difficult to excavate and driving. Moreover, the Static Load Tests for estimating the bearing capacity of pile foundations do not show accurate records in frozen soil. To solve the problems mentioned above, a special antifreeze composition has been developed and established its protective effect against soil freezing in winter. The implementation of the proposed method leads to a high productivity of driving reinforced concrete piles without the risk of their destruction. This eliminates the need for additional drilling works and more powerful and expensive rock drills, if the soil is protected from freezing. According to a special formula, the optimal mass of antifreeze is calculated, which allows protecting the soil without harming not only the soil, but also the structure of the concrete pile and the environment. During the static load test, piles driven into soil that had been covered with antifreeze has showed more accurate bearing capacity data. Scientific and experimental studies have established that antifreeze reduces the compressibility of frozen soil. © The Author 2021. This work is licensed under a Creative Commons Attribution License (https://creativecommons.org/licenses/by/4.0/) that allows others to share and adapt the material for any purpose (even commercially), in any medium with an acknowledgement of the work's authorship and initial publication in this journal. Проектирование, строительство и обслуживание свайных фундаментов зависят от особых погодных условий в северной и центральной частях Казахстана. Зимние месяцы в этих местах очень длинные, с ноября по март, а температура воздуха обычно достигает -40-50 ° C. Эти обстоятельства приводят к сезонному промерзанию грунта, особому физическому поведению грунта, физическим свойствам строительных материалов. Основная проблема забивки свай зимой - это мерзлый грунт, который трудно выкапывать и забивать.
Keywords: импакт-фактор 2021; скопус; scopus; сваи; зарубежное издание; дальнее зарубежье; научный журнал; периодическое издание; свайные фундаменты; строительство; строительные материалы